Antioxidant and Antiproliferative Potential of Acacia auriculiformis Methanol Leaves Extract Against Breast Cancer Cell Model - Triska Desi Sundari; Nastiti Wijayanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Acacia auriculiformis is a plant which often found in Indonesia. Acacia leaves have been known to have high antioxidant content. The phenolic compound of A. auriculiformis is the largest of these plants and phenolic compound have potential as anticancer protective agents. The aims of this study were to determine the phenolic compound, antioxidant activity, cytotoxic and antiproliferative activity of acacia leaves extract against T47D and MCF-7 breast cancer cell lines. Extraction was carried out by maceration method using methanol as a solvent. Phenolic compounds were examined by Thin Layer Chromatography (TLC) and antioxidant activity was measured using DPPH assay, followed by cytotoxicity and antiproliferation test measured by MTT Assay to obtain the IC50 value and percent of antiproliferation. Based on TLC, A. auriculiformis methanol leaves extract contain a phenolic compound with Rf value of 0.85 compared to gallic acid. ÃÂ Antioxidant activity A. auriculiformis with IC50 value of 9 ppm is classified as high antioxidant activity and MTT assay results for cytotoxicity with IC50 value of 273.8 and 31.26 ppm for T47D and MCF-7 cells, respectively. Antiproliferative analysis also showed high values for MCF-7 cells. These data have shown that methanol leaves extract of A. auriculiformis has high antioxidant activity and inhibited MCF-7 cell proliferation but not T47D breast cancer cell lines.ÃÂ